2006
DOI: 10.7202/012156ar
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Work Environment and Certified Sick Leave among Nurses during Organizational Changes and Downsizing

Abstract: The study aimed to determine whether the incidence and duration of certified sick leave (CSL) among nurses had increased during major restructuring of the health care system in the province of Québec, and to determine whether nurses exposed to adverse psychosocial factors at work showed an increased incidence of CSL. It involved nurses working in 13 health facilities. Sickness absence data were retrieved from administrative files (n = 1454). Incidence of CSL for all diagnoses and for mental health problems was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 42 publications
4
52
0
1
Order By: Relevance
“…At the employee level, research has established the effects of economic insecurity on physical health (e.g. Bourbonnais, Brisson, Vezina, Masse & Blanchette, 2005;Kim, 2003) and mental health (e.g. Kondilis et al, 2013) raising questions about employee and manager behavior in the workplace in difficult economic times (Galanaki & Papalexandris, 2013;Kanellopoulos, 2012).…”
Section: Factors Inhibiting Voice In An Economic Crisis Contextmentioning
confidence: 99%
“…At the employee level, research has established the effects of economic insecurity on physical health (e.g. Bourbonnais, Brisson, Vezina, Masse & Blanchette, 2005;Kim, 2003) and mental health (e.g. Kondilis et al, 2013) raising questions about employee and manager behavior in the workplace in difficult economic times (Galanaki & Papalexandris, 2013;Kanellopoulos, 2012).…”
Section: Factors Inhibiting Voice In An Economic Crisis Contextmentioning
confidence: 99%
“…The first contributor to difficult accommodations, managerial bias, has been acknowledged in previous research (e.g., Bourbonnais et al, 2005;Jackson, Furnham and Willen, 2000). The unique contribution here comes from detailed content analysis which revealed that bias could stem from the additional burden of accommodation, or could originate with distrust that springs up quickly and spreads from one disability situation to the next.…”
Section: Resultsmentioning
confidence: 88%
“…When negative attitudes prevail, employees believe managers may try to get rid of them (Slack, 2000) or may use resistance strategies to discourage them from requesting accommodation (Harlan and Robert, 1998). Low levels of supervisor support are also associated with reduced RTW rates (Krause et al, 2001b), increased lost time (Feuerstein et al, 2001) and increased use of sick time (Bourbonnais et al, 2005). However, some reviews have suggested that evidence of the impact of managerial support is not conclusive (Geertje, 2001).…”
Section: Managerial Attitudementioning
confidence: 99%
“…It is also interesting to mention that, in industrialized working populations, musculoskeletal symptoms and mental health problems are among the primary causes of work leave due to sickness (Bourbonnais et al 2005;Karttunen 1995;Vézina et al 2006;Vinet 2004). Since a day of absence costs up to 1.5-2 times the day's salary for the worker, a reduction in the prevalence of these health issues may have an important economic impact (Brun and Lamarche 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders, including arthritis, constitute the most common chronic condition (Lawrence et al 1998) and one of the leading causes of activity limitations (National Center for Health Statistics 2007). Musculoskeletal disorders and mental health problems have reached alarming prevalence and constitute the two main motives of work absence for a certified medical condition, causing considerable loss of productivity for employers (Bourbonnais et al 2005;Karttunen 1995;Niedhammer et al 1998;Vézina et al 2006;Vinet 2004).…”
Section: Contextmentioning
confidence: 99%